SOME FEATURES OF MORPHOFUNCTIONAL STATUS OF PERPHERAL BLOOD PLATELETS IN DONORS AND RECIPIENTS OF RENAL ALLOGRAFT - I. A. Vasilenko (Vestnik Transplantologii i Iskusstvennyh Organov, 2009)
The morphofunctional status of peripheral blood platelets from 16 recipients, 16 optimal and 16 marginal donors renal allograft were investigated by method of vital computer phase morphometry (phase-interference microscope «Cytoscan»). The abnormality of platelet hemostasis was found out in recipients and potential renal allograft donors. Such hemostasis damages can promote the thrombotic complications and failure of microcirculation in renal parenchymatous tissue.